2016
DOI: 10.1111/ddi.12423
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating resilience of tree communities in fragmented landscapes: linking functional response diversity with landscape connectivity

Abstract: These authors contributed equally to this work.ABSTRACT Aim Multiple agents of change increasingly impact functioning of forest ecosystems, for which management plans often ignore how local disturbances and habitat fragmentation jointly operate on ecological resilience at different scales. We examined sensitivity of functional response diversity (FD) to variation in species diversity to predict ecological resilience to future disturbances across tree communities and evaluated the role of landscape connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 107 publications
0
37
0
Order By: Relevance
“…Our findings of strong landscape-scale drivers of resilience are important as they complement previous assessments of Norway spruce resilience at the tree and stand scale, identifying stand age and density (Seidl et al 2017b) as well as site conditions, most notably water availability (Boden et al 2014;Zang et al 2014) as the key drivers of resilience to climate change. Consequently, the consideration of multiple spatial scales is crucial for a comprehensive assessment of ecosystem resilience (Craven et al 2016). In this context it is noteworthy that effects of individual processes on resilience can vary on different spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of strong landscape-scale drivers of resilience are important as they complement previous assessments of Norway spruce resilience at the tree and stand scale, identifying stand age and density (Seidl et al 2017b) as well as site conditions, most notably water availability (Boden et al 2014;Zang et al 2014) as the key drivers of resilience to climate change. Consequently, the consideration of multiple spatial scales is crucial for a comprehensive assessment of ecosystem resilience (Craven et al 2016). In this context it is noteworthy that effects of individual processes on resilience can vary on different spatial scales.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Higgins and Scheiter () showed that the impacts of abrupt, small‐scale regime shifts in vegetation cover are decreased at a landscape‐level due to their asynchrony and Craven et al. () demonstrated how interactions between local response diversity and habitat connectivity affect landscape‐level resilience of a temperate forest. Furthermore, a multi‐trophic, large‐scale study recently showed that ecosystem functioning drivers at small scales likely differ from those at larger scales: while identity and niche complementarity effects drove small‐scale ecosystem productivity, ecosystem functioning at larger scales was only directly associated with total biomass and species richness (Barnes et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the recognition that adaptive capacity is necessary to allow forest ecosystems to respond to unexpected events and to continue ensuring the provision of desired functions and services (Puettmann 2014), especially in an increasingly uncertain future. This aspect is reflected in the appreciation of the value of variability and diversity as key components for adaptive capacity (Conrad 1983). Thus, they become prominent considerations in silvicultural prescriptions.…”
Section: Managing Forests As Complex Adaptive Systems: Overcoming Thementioning
confidence: 99%